On resonant Neumann problems: Multiplicity of solutions - Papageorgiou, Nikolaos S. (2011)
We consider a semilinear Neumann problem with an asymptotically linear reaction term. We assume that resonance occurs at infinity. Using variational methods based on the critical point theory, together with the reduction technique and Morse theory, we show that the problem has at least four nontrivial smooth solutions.